(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
One of the best ways to protect metals from corrosion is the use of corrosion inhibitors. The use of inhibitors can only slow down corrosion, but cannot completely stop it[1,2]. Corrosion is one of the processes that cause great damage not only to industry, but also to material and spiritual heritage. According to their types, corrosion inhibitors are divided into anodic, cathodic and mixed corrosion inhibitors [3,4]. In general, there are several types of corrosion, which are characterized by the source of origin and properties. In preventing corrosion, the use of corrosion inhibitors can allow us to use structures for a relatively longer period of time, but it cannot completely eliminate this problem [5,6].